The construction of masculinity in male students' talk on (heterosexual) rape in South Africa: a discourse analysis - Everitt-Penhale, Brittany (Department of Psychology, 2015)
One in three South African women will be raped in her lifetime; the gravity of this issue makes investigating factors influencing rape perpetration a crucial endeavour. Drawing on a feminist post-structuralist framework, this study is based on the assumption that how masculinity is constructed in a given context may influence some men's sexually aggressive behaviour within that context. Six focus group sessions, each consisting of between four and six male university students (with a total of 30 participants) were held, in which the reasons for why some men rape in South Africa were discussed. Focusing on constructions of masculinity and heterosex, the data was analysed using discourse analysis based on the Foucauldian notion of discourse. The data was divided into three main sections, namely 'the Discourse of the Male Sexual Drive', 'Heterosex', and 'Masculinity as Power'. Consistent with previous literature, within the data the male sexual drive was constructed as being largely out of men's control, with men depicted as not being culpable for raping when they do not have access to consensual sex; when the victim is wearing revealing clothing; or when the victim is drunk. Heterosex was also constructed as having considerably different meaning for males and females, with a clear presence of the 'sexual double standard', in which men are praised for having sex whereas women are denigrated and seen as morally lacking. The rules of heterosexual conduct were also constructed as being mediated by culture, in ways in which it was argued ignore the individual rights and responsibilities of the victims and perpetrators of sexual violence. Having power was further constructed as the principle feature of masculinity, with rape being a means of attaining power. Therefore, men without access to power in other areas (primarily poor and/or black men) were depicted as being the most likely to rape. Rape was also seen as a response to women's empowerment, as well as a mechanism through which women that are "too proud" can be humbled, and was thereby constructed as a tool through which male power over women is maintained. It is argued that some of the constructions within the data are problematic in that they support racist, classist and patriarchal ideologies; often place the blame for rape entirely onto women, whose rights are at times ignored; and remove culpability from the perpetrators of rape. The findings of this study therefore demonstrate the importance of challenging accepted rape myths and underlying assumptions about masculinity and heterosex in order to address the issue of rape in South Africa